Nurses' Workplace Social Capital and the Influence of Transformational Leadership: A Theoretical Perspective - Xu, Jia-Min; Stark, Azadeh T.; Ying, Bi-He; Lian, Zheng-Mei; Huang, Yang-Sheng; Chen, Rui-Ming (Frontiers in Public Health, 2022)
Workplace social capital is the relational network, created by respectful interactions among members of a workforce, can contribute to the formation of a wholesome psychological work environment in an organization. Nurses' workplace social capital is a derivative of the workplace social capital, formed because of the complex interactions among the nursing and between the other healthcare professionals. Transformational leadership is a style of leadership that addresses the emotional wellbeing of its workforce and inspires shared group ethics, norms, and goals. The philosophy of transformational leadership is grounded on the premise of workforce as human beings with specific needs. Transformational leadership has been confirmed as a strong predictor of nurses' workplace social capital. Meanwhile, it is of an academic and/or healthcare industry operational value to scholarly assess and discern the theoretical influence of transformational leadership on nurses' workplace social capital. In this paper, we have attempted to explore the associations between transformational leadership and nurses' workplace social capital from a theoretical perspective. We have discussed the importance of each sub-dimension of transformational leadership (modeling the way, inspiring a shared vision, challenging the process, enabling others to act and encouraging the heart) in building up the social capital relational network. Finally, we have proposed a graphic framework of our analysis to facilitate understanding of the associations between the transformational leadership and nurses' workplace social capital, in formation of a healthy work environment which is the foundation for efficiency and productivity of the workforce.